Combined expression of HOXA11 and CD10 identifies endometriosis versus normal tissue and tumors - Bergman-Larsson Julia; Gustafsson Sofie; Méar Loren; Huvila Jutta; Tolf Anna; Olovsson Matts; Pontén Fredrik; Edqvist Per-Henrik D. (ELSEVIER SCIENCE INC, 2022)
The gold standard for diagnosing endometriosis is by laparoscopic visual demonstration of ectopic endometrial lesions outside the uterus, preferably verified by biopsy and microscopical examination. Molecular markers to facilitate the microscopical diagnosis of endometriosis and for distinguishing endometriosis from other benign and malignant lesions are lacking. Our aim was to test and validate an immunohistochemical antibody panel for improved diagnostic accuracy of endometriosis. Both CD10 and HOXA11 have been implicated in regulation of endometrial homeostasis. Here we have analyzed the expression pattern of these two proteins using immuno-histochemistry on human tissues in a tissue microarray format. CD10 and HOXA11 expression in endometriosis lesions were compared to expression patterns in a range of normal tissues and in primary-and metastatic lesions of endometrial-, cervical-and ovarian cancer. HOXA11 and CD10 were expressed in 98% and 91% of endo-metriosis lesions and the combined double-positive expression profile of both HOXA11 and CD10 was highly sensitive for ectopic endometrial tissue (90%). The specificity and sensitivity for this double-positive signature in endometriosis was significantly different from all investigated tissues, cancers and metastases except normal, eutopic endometrial-and cervical mucosa. The combination of HOXA11 and CD10 expression profiles provides a useful tool to identify ectopic endometrial tissue and for distinguishing endometriosis from various types of gynecological malignancies and metastases.